The Influences of Company’s Growth, Cash Flow, and Debt Default on the Acceptance of Going Concern Audit Opinions - Annisa Nurbaiti; Siska Ditya Mei Yanti (The Indonesian Journal of Accounting Research, 2022)
A going concern audit opinion is a modified assumption given by the auditor for a company that represents material doubts or uncertainties about its ability to continue operations. This study intends to provide empirical evidence regarding the simultaneous and partial effects of company growth, cash flow, and debt default on acceptance of going concern audit opinions in coal subsector companies listed on the Indonesia Stock Exchange in 2016-2020. Sampling was selected using a purposive sampling technique, obtained 18 companies from 90 data that met the criteria. Hypothesis testing was carried out using descriptive analysis and logistic regression. The results showed that company growth, cash flow, and debt default simultaneously affected the acceptance of going-concern audit opinions. Partially, the company's growth does not affect the acceptance of going-concern audit opinions. Conversely, cash flow has a negative effect on receiving going-concern audit opinions, and debt default positively affects receiving going-concern audit opinions. This research is expected to provide further information regarding the factors influencing the receipt of a going concern audit opinion. These factors can be used by company management as evaluation material to avoid receiving a going concern audit opinion by paying more attention to the company's financial performance and soundness, especially cash flow and debt defaults. For investors, the research results can be used as a wiser consideration when investing in companies with poor cash flow and default status.